Богдан Іванович Ханенко (1849 – 1917 рр.) - Половець, В. (Сiверянський лiтопис, 2009)
У статті розглянуто становлення Богдана Івановича Ханенка як колекціонера, мецената та організатора музейної справи в Києві. Дворянин Чернігівської губернії, який співчував різночинно-інтелігентській ідеї, став прикладом служіння народу, обравши метою свого дослідження художній живопис. У широкому залученні до цього він бачив запоруку розвитку народної освіти. В статье рассматривается становление Богдана Ивановича Ханенка как коллекционера, мецената и организатора музейного дела в Киеве. Дворянин Черниговской губернии, который сочувствовал разночинно-интелигентской идее, стал примером служения народу, избрав целью своего исследования художественную живопись. В широком приобщении к ней он видел залог развития народного просвещения. The article deals with Bohdan Ivanovych Khanenko, his becoming a collector, Maccenas and organizer of the museum business in Kyiv. A nobleman of Chernihiv gubernia, who sympathized with the men of different rank intelligent ideas became an example of serving the people having chosen painting an object of his investigation. His wide involvement in painting was considered to be a pawning of popular education developmen.